FEAR OF MAKING MISTAKES AS A PSYCHOLOGICAL BARRIER IN ESL CLASSROOMS - Kosimov Bunyod Kosim o’g’li, (TADQIQOTLAR, 2025)
Abstract Making  mistakes  is  widely  recognized  as  an  essential  component  of  second language acquisition. Nevertheless, many learners of English as a Second Language (ESL) experience a strong fear of making mistakes, which can significantly hinder their communicative development. Despite possessing adequate linguistic knowledge, such learners often remain silent or overly cautious in classroom interactions. This paper argues that fear of making mistakes constitutes a major psychological barrier in ESL learning.  It  examines  the  underlying  causes  of  this  fear,  its  effects  on  language acquisition, and pedagogical strategies that teachers can employ to reduce learners’ anxiety and foster a more supportive learning environment.